Contributions to the taxonomy, identification, and biogeography of Palaearctic Campopleginae (Hymenoptera: Ichneumonidae), with the descriptions of four new species from Iran - Vas, Zoltán; Rezaei, Shoreh; Fallahzadeh, Majid; Mohammadi-Khoramabadi, Abbas; Saghaei, Nazila; Ljubomirov, Toskho (Zootaxa, 2022)
In this paper four new species of Campopleginae (Ichneumonidae) are described from Iran: Campoletis rubella Vas, sp. nov., Cymodusopsis riedeli Vas, sp. nov., Lemophagus eburnipes Vas, sp. nov., and Melalophacharops persicus Vas, sp. nov. An identification key to the Palaearctic species of Cymodusopsis Viereck is given. Campoletis katalinarum Vas and Lemophagus foersteri (Tschek) are first reported from the Eastern Palaearctic region.